Creditors’ Use of Consumer Debt Criminalization Practices and their Financial Abuse of Women - Johnson, Creola (Columbia Journal of Gender and Law, 2016)
In 1998, while a practicing attorney, I helped a legal aid client file for Chapter 7 bankruptcy relief because she was no longer able to manage her debts. As required under bankruptcy law, I had to help her file a list of all her creditors, as well as a statement of intention, which provides a snapshot as to how certain debts will be treated. My client, “Brenda,” a single mother, became fearful as I discussed with her the possibility of not paying a rent-to-own (“RTO”) company from which she had obtained a living room set. She told me that we had to pay the company because, as she said, “I don’t want them to put me in jail.” I was completely dumbfounded that she thought that could really happen to her. I explained to her that the RTO company could not put her in jail for failing to pay a civil debt. But she insisted we had to pay because, “I’m not going to jail.” Little did I know I was really the ignorant one.